Milk production and quality of Etawa crossbreed dairy goat that given Tithonia diversifolia, corn waste and concentrate based palm kernel cake - Arief ARIEF; RUSDIMANSYAH RUSDIMANSYAH; SIMEL SOWMEN; RONI PAZLA; RIZQAN RIZQAN (Society for Indonesian Biodiversity, 2020)
Abstract. Arief, Rudimansyah, Sowmen S, Rizqan RP. 2020. Milk production and quality of Etawa crossbreed dairy goat that given Tithonia diversifolia, corn waste and concentrate based palm kernel cake. Biodiversitas 21: 4004-4009. The research aims to evaluate the production and quality of goat milk of Etawa crossbreed dairy goat (ECDG) which is fed by Tithonia diversifolia (T), corn waste (CW), and concentrate-based palm kernel cake (CBP),. The experimental design used in this study was a completely random design (CRD) with four times treatment rations and five times replications. There are five treatments used in this research which are; treatment A used 60 % T + 40 % tofu-dregs; B used 60 % T + 20% tofu-dregs + 20% CBP; C used 45 % T + 15% CW + 20% tofu-dregs + 20% CBP; D used 30 % T + 30% CW + 20% tofu-dregs + 20% CBP. The data were analyzed by Analysis of Varian (ANOVA) and Duncan's Multiple Range Test (DMRT) for further tests. The parameters measured were milk production and milk quality, which covers dry matter, water content, protein, fat, solid non-fat, and lactose. The result showed that the treatment gave no significant effect (P> 0.05) of milk production, dry matter, protein, fat, solid non-fat, and lactose. The study concluded that the use of T. diversifolia, corn-waste, and CBP could maintain milk production quality.